Surgical outcomes of different approaches in robotic assisted thyroidectomy for thyroid cancer: A systematic review and Bayesian network meta-analysis. (May 2021) - Xing, Zhichao; Qiu, Yuxuan; Abuduwaili, Munire; Xia, Baoying; Fei, Yuan; Zhu, Jingqiang; Su, Anping
Abstract: Background: The aim of the study was to assess the feasibility, safety, and potential benefits of four approaches of robotic assisted thyroidectomy (RT). The approaches mentioned above are also compared with traditional open thyroidectomy (OPEN). Materials and methods: Medline, Embase, Cochrane library (CENTRAL) and Web of Science databases were searched up to 13th Dec 2019. Data of surgical outcomes and complications were extracted to conduct the statistical analyses. Results: A total of 30 studies with 6622 patients were included. Ten were prospective study and 1 declared prospective randomized comparative study. The number of retrieved lymph nodes (LNs) in central compartment were similar between gasless transaxillary approach (GAA), bilateral axillo-breast approach (BABA) and transoral approach (OA). OPEN retrieved more LNs than BABA and OA. More metastatic LNs were seen in GAA and BABA than OA, as was for OPEN. The operation time was significantly shorter in GAA and gasless unilateral transaxillary approach (GUAA) than BABA and OA, while shortest for OPEN. Lower incidence of transient hypoparathyroidism was found in BABA than OPEN. No significant difference was observed in other indexes. Conclusions: BABA, GAA, GUAA and OA in RT appear to be feasible and safe for patients with thyroid cancer with unique benefits. Surgical outcomes of different approaches were not identical for operation time, cosmetic effects, central neck dissection. Surgeons would consider more about patients' will. Highlights: Open thyroidectomy retrieved more metastatic lymph nodes than robotic thyroidectomy. The operative time was short in traditional open thyroidectomy. The rate of transient hypoparathyroidism was low in bilateral axillo-breast approach.